Teaching about genocide. Volume 1 : insights and advice from secondary teachers and professors / edited by Samuel Totten. - Totten, Samuel (Rowman & Littlefield, 2018)
"Secondary level teachers and professors from various disciplines present their best advice and insights into teaching about various facets of genocide and/or delineate actual lessons they have taught that have been particularly successful with their students"--Publisher's description.
Keywords: Genocide -- Study and teaching (Secondary); Genocide -- Study and teaching (Secondary) -- Case studies.; Case studies.